2017
DOI: 10.1155/2017/1017584
|View full text |Cite
|
Sign up to set email alerts
|

A Single Centre Experience of Day Case Laparoscopic Cholecystectomy Outcomes by Body Mass Index Group

Abstract: Aim The purpose of this study was to evaluate whether patients with a high BMI can undergo safe day case LC for cholecystitis compared to groups of patients with a lower BMI. Setting NHS District General Hospital, UK. Methods A retrospective review of 2391 patients who underwent an attempted day case LC between 1 January 2009 and 15 August 2015 was performed. Patients were divided into five groups depending on their BMI. Inclusion criteria were patients undergoing elective day case laparoscopic cholecystectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
(5 reference statements)
1
6
0
Order By: Relevance
“…Gregori et al 37 showed that obesity is not a contributory variable for postoperative complications and prolonged hospital admission. In keeping with Gregori et al, Bowling et al 38 reported that the overall complication rate was equivalent between different BMI groups, and the majority of patients with BMI >30 Kg/m 2 can be planned and successfully complete LC with early discharge ≤24 hours. Even though a limited number of patients were obese in our cohort, we have shown that increased BMI was not associated with worse outcomes after day-case LC.…”
Section: Discussionsupporting
confidence: 62%
“…Gregori et al 37 showed that obesity is not a contributory variable for postoperative complications and prolonged hospital admission. In keeping with Gregori et al, Bowling et al 38 reported that the overall complication rate was equivalent between different BMI groups, and the majority of patients with BMI >30 Kg/m 2 can be planned and successfully complete LC with early discharge ≤24 hours. Even though a limited number of patients were obese in our cohort, we have shown that increased BMI was not associated with worse outcomes after day-case LC.…”
Section: Discussionsupporting
confidence: 62%
“…Surgical factors analysed included single port LC vs. four port LC [ 13 , 29 , 42 ] (OR = 1.27, CI = 0.83–1.96, P = 0.27) ( Figure 7 ), and day case LC vs. inpatient LC [ 17 , 37 ] (OR = 0.50, CI = 0.16–1.53, P = 0.23) ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the unplanned readmission was defined as any use of emergency department, outpatient department, or other medical services during 30 days after the procedure, except prolonged hospital stay [ 17 ].…”
Section: Methodsmentioning
confidence: 99%